Chlorogenic Acid Attenuates Dextran Sodium Sulfate-Induced Ulcerative Colitis in Mice through MAPK/ERK/JNK Pathway. (18th April 2019) - Gao, Wenyan; Wang, Changhong; Yu, Li; Sheng, Tianjiao; Wu, Zhuolin; Wang, Xiaoqian; Zhang, Dongqi; Lin, Yifan; Gong, Yang
Abstract : Objective . Observe the protective effect of chlorogenic acid on dextran sulfate-induced ulcerative colitis in mice and explore the regulation of MAPK/ERK/JNK signaling pathway. Methods . Seventy C57BL/6 mice (half males and half females) were randomly divided into 7 groups, 10 in each group: control group (CON group), UC model group (UC group), and sulfasalazine-positive control group (SASP group), chlorogenic acid low dose group (CGA-L group), chlorogenic acid medium dose group (CGA-M group), chlorogenic acid high dose group (CGA-H group), and ERK inhibitor + chlorogenic acid group (E+CGA group). The effects of chlorogenic acid on UC were evaluated by colon mucosa damage index (CMDI), HE staining, immunohistochemistry, ELISA, and Western blot. The relationship between chlorogenic acid and MAPK/ERK/JNK signaling pathway was explored by adding ERK inhibitor. Results . The UC models were established successfully by drinking DSS water. Chlorogenic acid reduces DSS-induced colonic mucosal damage, inhibits DSS-induced inflammation, oxidative stress, and apoptosis in colon, and reduces ERK1/2, p -ERK, p38, p-p38, JNK, and p-JNK protein expression. ERK inhibitor U0126 reversed the protective effect of chlorogenic acid on colon tissue. Conclusion . Chlorogenic acid can alleviate DSS-induced ulcerative colitis in mice, which can significantly reduce tissue inflammation and apoptosis, and its mechanism is related to the MAPK/ERK/JNK signaling pathway.